Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1089/jpm.2011.0410
|View full text |Cite
|
Sign up to set email alerts
|

Parents' Thoughts and Perceptions on Hearing that Their Child Has Incurable Cancer

Abstract: When parents were told that their child had incurable cancer, their first thought was to protect their child. Because thoughts and perceptions in such a situation vary across parents, health care professionals should support parents in realizing their thoughts and perceptions and in making decision as parents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 36 publications
0
37
0
1
Order By: Relevance
“…48,80,52,81,82 These parents are attempting to fulfill an integral role as caregiver – protecting and caring for their children. 62,83 In a recent qualitative study of 18 Romanian parents of children with cancer, parents reported three factors that contributed to restricted communication with their child: information overload and emotional turmoil, lack of knowledge and skills for disclosing the diagnosis, and assumptions about burdening the child when discussing cancer. 82 To fully understand parental behavior, clinicians should give attention to “the reason and emotion they bring to decision-making and their children’s care, their unique responsibilities as parents, and what they learn throughout the illness.” 84 …”
Section: To Tell or Not To Tell – Growing Appreciation Of Complexitymentioning
confidence: 99%
“…48,80,52,81,82 These parents are attempting to fulfill an integral role as caregiver – protecting and caring for their children. 62,83 In a recent qualitative study of 18 Romanian parents of children with cancer, parents reported three factors that contributed to restricted communication with their child: information overload and emotional turmoil, lack of knowledge and skills for disclosing the diagnosis, and assumptions about burdening the child when discussing cancer. 82 To fully understand parental behavior, clinicians should give attention to “the reason and emotion they bring to decision-making and their children’s care, their unique responsibilities as parents, and what they learn throughout the illness.” 84 …”
Section: To Tell or Not To Tell – Growing Appreciation Of Complexitymentioning
confidence: 99%
“…Besides the expansion of caregiving tasks, these studies show that parents have to deal with uncertainty and to adapt to an accumulation of losses related to their child’s physical and functional decline [ 6 , 14 , 26 ]. Although parents intend to act in their child’s best interest, including a good death, many of them struggle with facing reality and the timely transition from preserving their child at all costs towards being prepared to let their child die [ 2 , 10 , 14 , 16 , 23 ]. Moreover, parents emphasise they have to ‘navigate uncharted territory’ and lack professional guidance, resulting in feelings of isolation and abandonment [ 15 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare professionals (HCP) play a pivotal role in involving teenagers in decisions about their care and treatment . Clinical teams work with both teenagers and their families in decision making, communicating information to them, seeking their opinions and incorporating these into treatment plans.…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare professionals (HCP) play a pivotal role in involving teenagers in decisions about their care and treatment. 1,2 Clinical teams work with both teenagers and their families in decision making, communicating information to them, seeking their opinions and incorporating these into treatment plans. Yet, there has been little research on HCP real-time views of involving teenagers, how those views may Abbreviations: CNS, clinical nurse specialist; HCP, healthcare professionals; IC, Informal conversation; MDT, multi-disciplinary team; TYA, teenage and young adult This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.…”
Section: Introductionmentioning
confidence: 99%